BOYCOTT EFFECTIVENESS: THE DYNAMICS OF CONSUMER PREFERENCES - Chindagafika, Aydinarafa Nabila; Febrianti, Gevin Nadila (Jurnal Pijar, 2024)
Boycotts against multinational companies considered affiliated with Israel such as Unilever have attracted the attention of Indonesians who are consumers of these companies. This study aims to analyze the effectiveness of the boycott on consumer preferences and decisions in choosing substitute products. This study uses quantitative methods, the data is analyzed using paired sample t-test and multiple linear regression. The results showed that consumers' perception of Unilever decreased significantly after the boycott (p < 0.05). In addition, consumers' concern about the boycott was shown to have a significant effect on the decision to choose a substitute product (p < 0.05). This study shows that boycotts can affect consumer preferences for purchasing products and consumer concern also affects purchasing decisions